Multi-modality Imaging of a relapsing Mycotic post-infarction left ventricular pseudoaneurysm after surgical repair - Mantini, Cesare; Olivieri, Marzia; Di Mascio, Valeria; Procaccini, Luca; Ricci, Fabrizio; Cademartiri, Filippo (Acta Biomedica Atenei Parmensis, 2022)
Mycotic left ventricular pseudoaneurysm (LVP) is an uncommon life-threatening condition, resulting from myocardial rupture contained by the pericardium or scar tissue. Myocardial infarction is the leading cause of LVP, followed by cardiac surgery, previous chest trauma and infections. We present a case of a 69-year-old woman who developed a relapsing post-infarction LVP arising from mid infero-septal left ventricular wall. Such condition had been already treated with surgical repair 5-years earlier. Multiple non-invasive imaging modalities demonstrated its anatomy and localization. LVP is a challenging diagnosis due to the lack of specific symptoms and an insidious clinical presentation. Cardiac MR (CMR) allows an optimal LVP diagnosis due to its high spatial resolution and tissue characterization capabilities; CMR can also evaluate the pericardium, thrombi and the discontinuity of the myocardium. It is important to reduce the risk of LVP rupture; surgical repair is indicated in all acute cases of myocardial infarction. In chronic cases surgical repair is indicated for symptomatic patients, those diagnosed recently (<3 months), and those with large (>3 cm) or progressively expanding pseudoaneurysms.